HUBUNGAN KARAKTERISTIK IBU BERSALIN DENGAN PREEKLAMPSIA BERAT DI RSU A PURWAKARTA TAHUN 2020 - Rukiah, Ai Yeyeh; Sari, Daris Yolanda; Humaeroh, Dita (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2021)
This study was to determine the corellation between maternal characteristics and severe preeclampsia at RSU A Purwakarta. This research design uses descriptive analytical research method with cross-sectional. The data used is secondary data from medical records. The variables studied included: maternal age, parity, history of hypertension, gestational age. The population taken was women giving birth with severe preeclampsia who gave birth by CS or spontaneously. Samples taken as many as 130 from 192 populations. Sampling using simple random sampling technique is described by using bivariate technique.. The results showed that the corellation of preeclampsia on the type of delivery that was significant (p value <0.05) was gestational age with a P-value of 0.010. While the factors that did not correlation were maternal age, parity, gemelli pregnancy, history of hypertension, and LBW. Pregnancy can affect the incidence of preeclampsia in women with childbirth at the A Purwakarta General Hospital.